Educational Facilities for the Twenty-First Century Research Analysis and Design Patterns - Moore, Gary T.; Lackney, Jeffery A.; Wisconsin Univ., Milwaukee. School of Architecture and Urban Planning ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This handbook examines the relationship between school buildings and educational performance. Following the introductory chapter, chapter 2 presents findings from empirical studies that have examined the building/performance issue. Research has demonstrated that the physical setting has both direct and mediated effects on prosocial and achievement outcomes. Chapter 3 presents an ecological model that accounts for physical, psychological, and social environmental factors that affect student outcomes. The fourth chapter offers an analysis based on a review of empirical research, architectural literature, and educational reform literature to inductively develop a set of 27 design patterns. Two patterns based on environment-behavior research are highlighted--small schools and well-defined activity pockets. Chapter 5 discusses implications from the educational reform literature. The complete set of 27 patterns is presented in the sixth chapter. Chapter 7 presents an example that uses patterns to create a prototypical design for a new type of educational facility. The final chapter focuses on the earlier stages of the facility development process, those of feasibility and planning. A reconceptualization of an existing educational facility planning model is offered. A total of 42 figures and 1 table are included. (LMI)
Availability: Center for Architecture and Urban Planning Research, University of Wisconsin-Milwaukee, Milwaukee, WI 53201-0413 (Report No. R94-1
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Environment; Educational Facilities Design; Educational Facilities Improvement; Educational Facilities Planning; Elementary Secondary Education; Institutional Environment; School Buildings; School Size; School Space; Guides, Non-Classroom.; Reports, Research